Pengembangan Model untuk Memprediksi Kontribusi Ekonomi dari Kunjungan Wisatawan - Priyanto -; Wahyudi Sutopo (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2007)
Industrial Tourism in Town of Bandung not yet earned to give output (performasi of system) which can give economic contribution which isn't it. This research aim to for the development of mathematical model to predict of economic contribution of tourist visit. Development of this mathematical model will start with correlational research. This model is expected good for developing proposal for the agenda of improving performance of system existing as according to policy of public Development of Tourism and Culture Of Town of Bandung. On duty tourism can use proposal model to improve tourism performance. One of the program proposal the lifted is